Assessment of marine ecosystem services indicators: Experiences and lessons learned from 14 European case studies. (6th July 2016) - Lillebø, Ana I; Somma, Francesca; Norén, Katja; Gonçalves, Jorge; Alves, M Fátima; Ballarini, Elisabetta; Bentes, Luis; Bielecka, Malgorzata; Chubarenko, Boris V; Heise, Susanne; Khokhlov, Valeriy; Klaoudatos, Dimitris; et al.
ABSTRACT: This article shares the experiences, observations, and discussions that occurred during the completing of an ecosystem services (ES) indicator framework to be used at European Union (EU) and Member States' level. The experience base was drawn from 3 European research projects and 14 associated case study sites that include 13 transitional‐water bodies (specifically 8 coastal lagoons, 4 riverine estuaries, and 1 fjord) and 1 coastal‐water ecosystem. The ES pertinent to each case study site were identified along with indicators of these ES and data sources that could be used for mapping. During the process, several questions and uncertainties arose, followed by discussion, leading to these main lessons learned: 1) ES identification: Some ES that do not seem important at the European scale emerge as relevant at regional or local scales; 2) ES indicators: When direct indicators are not available, proxies for indicators (indirect indicators) might be used, including combined data on monitoring requirements imposed by EU legislation and international agreements; 3) ES mapping: Boundaries and appropriate data spatial resolution must be established because ES can be mapped at different temporal and spatial scales. We also acknowledge that mapping and assessment of ES supports the dialogue between human well‐being and ecological status. From an evidence‐based marine planning‐process point of view, mapping and assessment of marine ES are of paramount importance to sustainable use of marine natural capital and to halt the loss of marine biodiversity. Integr Environ Assess Manag 2016;12:726–734. © 2016 SETAC Key Points: The provisional accompanying classification table of abiotic outputs from natural systems can be very useful for the marine ecosystems assessment in support of ecosystems management and governance. Mapping can be a powerful tool for managers and policy‐makers. The integration of indicators or their proxies should be fostered across different components of European Union legislation and international agreements. Mapping needs to be coupled with additional knowledge on the functioning of marine ecosystems